The global, regional, and national burden attributable to low bone mineral density, 1990–2020: an analysis of a modifiable risk factor from the Global Burden of Disease Study 2021 - GBD 2021 Low Bone Mineral Density Collaborators (Elsevier BV, 2026)
Background: Fractures related to osteoporosis and low bone mineral density lead to substantial morbidity, mortality, and cost to individuals and health systems. Here we present the most up-to-date global, regional, and national estimates of the contribution of low bone mineral density to the burden of fractures from falls and additional categories of injuries from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021.
Methods: The burden of low bone mineral density was estimated from 1990 to 2020 in terms of years lived with disability (YLDs), disability-adjusted life years (DALYs), and deaths, for individuals aged 40 years and older, using data from population-based studies from 48 countries or territories (169 unique sources). Mean standardised femoral neck bone mineral density values were estimated by GBD location, age, and sex by meta-regression. Based on a separate meta-analysis of population-based studies from nine countries (12 unique sources), we also estimated the pooled relative risk of fractures per unit decrease in bone mineral density (g/cm2). The population-attributable fraction for low bone mineral density was calculated by comparing the observed distributions of standardised femoral neck bone mineral density to an age-specific and sex-specific counterfactual distribution, defined as the 99th percentile of five rounds of the National Health and Nutrition Examination Survey in the USA, by 5-year age group and sex. Hospital and emergency department data were used to derive the incidence of fractures for six categories of injury (road injuries, other transport injuries, falls, non-venomous animal contact, exposure to mechanical forces, and physical interpersonal violence) using ICD codes. Deaths due to fractures were estimated as the proportion of in-hospital deaths due to the specified injury causes for which a fracture (nature of injury code) was more severe than the cause of injury code. YLDs and DALYs attributable to low bone mineral density by cause of injury were also determined according to previous GBD methods.
Findings: In 2020, 8·32 million (95% UI 5·58-10·84) YLDs, 17·2 million (14·1-20·2) DALYs, and 477 000 (411 000-536 000) deaths were attributable to low bone mineral density globally in individuals aged 40 years and older. Between 1990 and 2020, global YLDs, DALYs, and deaths attributable to low bone mineral density increased by 91·8% (88·5-95·1), 89·8% (81·5-99·0), and 127·1% (108·5-144·5), respectively. Over this period, the age-standardised global rates of YLDs, DALYs, and deaths attributable to low bone mineral density showed modest decreases. In 2020, falls accounted for 76·2% (95% UI 74·2-78·3) of YLDs, 65·2% (62·9-67·6) of DALYs, and 71·0% (67·4-72·8) of deaths attributable to low bone mineral density, and road injuries largely accounted for the remaining amount: 12·4% (11·1-13·6) of YLDs, 24·6% (22·5-27·1) of DALYs, and 23·1% (21·6-26·2) of deaths. As a proportion of all fall-related burden, low bone mineral density accounted for 26·6% (23·2-28·7) of YLDs, 25·6% (22·1-27·4) of DALYs, and 40·6% (35·4-44·0) of deaths in 2020. Of all road injury-related burden, 12·6% (10·8-13·5) of YLDs, 6·3% (5·4-6·9) of DALYs, and 8·9% (7·6-9·6) of deaths were attributable to low bone mineral density. In men, road injuries accounted for the largest proportion of DALYs attributable to low bone mineral density in those aged 40-59 years and the largest proportion of deaths in those aged 40-64 years. In women, road injuries were the leading cause of DALYs attributable to low bone mineral density in those aged 40-44 years and the leading cause of deaths attributable to low bone mineral density in those aged 40-54 years. In older age groups among both men and women, falls were the leading cause of the burden attributable to low bone mineral density.
Interpretation: Low bone mineral density is a crucial modifiable risk factor for fractures, which are an important cause of morbidity and mortality particularly in ageing populations. This analysis highlights low bone mineral density as a cause of health loss not just from falls, but also from road injuries.